Edo Tensei Pembelajaran Sejarah - Santosa, Nyong Eka Teguh Iman (Jurnal Sejarah Indonesia, 2023)
This paper highlights the urgency of prophetic epistemology in learning history. Without neglecting the contribution of learning styles that emphasize the notion of history as a scientific effort to find truthful facts in the past, prophetic epistemology can strengthen its relevance as something that is permanent and will always be needed in education. Through a reflective approach to the Naruto anime story that introduced the kinjutsu Edo Tensei, the main issues are analyzed within some philosophical frameworks on history. Conceptual elaboration is also carried out through contemplation of several Qur'anic verses related to history, namely surah al-Hashr verse 18, Yusuf 111, and al-Rum 9. It is concluded that learning history should be able to activate students' prophetic awareness that history is a critical reading of past events as well as a transformative engagement of the present with ethical commitment.